Penatalaksanaan Fisioterapi dengan Metode Latihan Plyometric Depth Jump untuk Meningkatkan Kekuatan Otot Tungkai pada Atlet Basket - Eftina Tri Amini; Adi Saputra Junaidi; Wanti Hasmar (3031-8572, 2022)
Explosive power is one of the important biomotor components in sports activities, because explosive power will determine how hard people can hit, how high they jump, how fast they run and so on. One of the plyometric exercises is the depth jump. Depth jump is an exercise performed by performing a maximum jump as soon as the athlete jumps down from a height. Depth jump is a plyometric exercise using additional equipment, namely a plyometric box. Objective: To find out the benefits of plyometric depth jump training on increasing the explosive power of leg muscles in basketball athletes. After the plyometric depth jump exercise, an increase in leg muscle explosive power for 4 times of therapy can be seen, the effect of the plyometric depth jump exercise on increasing muscle explosive power. Plyometric depth jump is more effective to increase leg muscle explosive power.